Active management of third stage of labour by oxytocin: Umbilical vein versus intramuscular use - Ojha, Neebha; Malla, Dibya S (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Aim: To compare oxytocin used via intraumbilical or intramuscular route in the active management of third stage of labour with respect to duration and amount of bleeding. Methods: Prospective comparative study conducted in Maternity Hospital, Thapathali, Kathmandu for three months 29th April - July 28th 2004 (061/1/16 to 061/4/12 BS ). After immediate umbilical cord clamping following vaginal delivery, 120 women were divided into 2 groups administering 10 units of oxytocin; in Group I: which was diluted mixing with 10 ml of normal saline before it was infused intraumbilical and Group II: injected intramuscularly. Results: There was no difference in the duration of third stage of labour (3.6 vs. 3.7min) between the two groups. There was significant blood loss in the intraumblical group as compared to intramuscular group (242ml vs.168ml, p. 0.004). The need for additional oxytocic to control the uterine bleeding was more in intraumbilical group as compared to intramuscular group (28.3% vs 6.7%, p 0.005). There was more postpartum haemorrhage (PPH) in intraumbilical group (8.3% vs 3.3%, p 0.439). The injection delivery interval was significantly longer in the intraumbilical group as compared to intramuscular group (46.9 vs. 30.7 sec). Conclusion: Intraumbilical oxytocin is technically more difficult to administer without having any added benefit either in decreasing the duration of third stage of labour or reducing the blood loss. Key words: Intraumbilical oxytocin, intramuscular oxytocin, third stage of labour. doi:10.3126/njog.v2i1.1469 N. J. Obstet. Gynaecol Vol. 2, No. 1, p. 13 - 16 May -June 2007